1987
DOI: 10.1111/j.1471-4159.1987.tb05757.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lactate Production in Rat Brain Extracts and Synaptosomes by 3‐[4‐(Reduced 3‐Pyridine Aldehyde‐Adenine Dinucleotide)]‐Pyruvate

Abstract: In basic solutions, pyruvate enolizes and reacts (through its 3-carbon) with the 4-carbon of the nicotinamide ring of NAD+, yielding an NAD-pyruvate adduct in which the nicotinamide ring is in the reduced form. This adduct is a strong inhibitor of lactate dehydrogenase, presumably because it binds simultaneously to the NADH and pyruvate sites. The potency of the inhibition, however, is muted by the adduct's tendency to cyclize to a lactam. We prepared solutions of the pyruvate adduct of NAD+ and of NAD+ analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Earlier studies had shown that 3-acetylpyridine nicotinamide adenine dinucleotide-pyruvate (ANAD-Pyr), a strong inhibitor of LDH, reduced lactate production in crude brain extracts, although the inhibitor was less effective in synaptosomes [9]. The main reason for the minimal effect in synaptosomes is likely associated with the hydrophilic nature of ANAD-Pyr and the low stability of the compound at physiological pH [9]. NADH-GA is also highly polar and very stable under physiological conditions and in contrast to ANAD-Pyr can not be degraded by LDH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier studies had shown that 3-acetylpyridine nicotinamide adenine dinucleotide-pyruvate (ANAD-Pyr), a strong inhibitor of LDH, reduced lactate production in crude brain extracts, although the inhibitor was less effective in synaptosomes [9]. The main reason for the minimal effect in synaptosomes is likely associated with the hydrophilic nature of ANAD-Pyr and the low stability of the compound at physiological pH [9]. NADH-GA is also highly polar and very stable under physiological conditions and in contrast to ANAD-Pyr can not be degraded by LDH.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in proton concentration initiates a cascade of events leading to apoptosis and cell death in cultured cells including cardiac myocytes [14,15,17,35,36]. Earlier studies had shown that 3‐acetylpyridine nicotinamide adenine dinucleotide‐pyruvate (ANAD‐Pyr), a strong inhibitor of LDH, reduced lactate production in crude brain extracts, although the inhibitor was less effective in synaptosomes [9]. The main reason for the minimal effect in synaptosomes is likely associated with the hydrophilic nature of ANAD‐Pyr and the low stability of the compound at physiological pH [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations